Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376554
|View full text |Cite
|
Sign up to set email alerts
|

Too Hot to Handle: An Evaluation of the Effect of Thermal Visual Representation on User Grasping Interaction in Virtual Reality

Abstract: Influence of interaction fidelity and rendering quality on perceived user experience have been largely explored in Virtual Reality (VR). However, differences in interaction choices triggered by these rendering cues have not yet been explored. We present a study analysing the effect of thermal visual cues and contextual information on 50 participants' approach to grasp and move a virtual mug. This study comprises 3 different temperature cues (baseline empty, hot and cold) and 4 contextual representations; all e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 113 publications
2
9
0
Order By: Relevance
“…For each condition, VHs asked participants to do the survey, which was Visual effects taxonomy to be used in our experiment. We reviewed the previous AR/VR researches [4], [13], [14], [17], [18], [27]- [42] and classified color (Low, High) and form (Exaggerated, Diminished) as 2 × 2 matrices with respect to VFX's visibility.…”
Section: B Materials 1) Physical Setupmentioning
confidence: 99%
“…For each condition, VHs asked participants to do the survey, which was Visual effects taxonomy to be used in our experiment. We reviewed the previous AR/VR researches [4], [13], [14], [17], [18], [27]- [42] and classified color (Low, High) and form (Exaggerated, Diminished) as 2 × 2 matrices with respect to VFX's visibility.…”
Section: B Materials 1) Physical Setupmentioning
confidence: 99%
“…Besides, Günther et al [29] designed a thermal display that provides warm and cold on-body feedback in VR through flowing liquids with different temperatures, and investigated the interdependency of visual and thermal perception in VR. Blaga et al [6] analyzed the effect of thermal visual cues on users' grasping actions without inducing actual thermal stimulus. Xu et al [96] reported a non-contact cold thermal display using a vortex tube to generate ultra-low air temperature.…”
Section: Haptic Rendering Of Abnormal Sensationmentioning
confidence: 99%
“…However, these limitations can be addressed by closely analysing human actions while grasping objects in VR [69]. Accordingly, Blaga et al [8] analysed human actions while grasping virtual objects by investigating the influence of thermal visual cues on grasping in VR, to understand how virtual environments influence grasping approaches. However, this study only investigated one virtual object (the mug) and was only looking at thermal visual cues.…”
Section: Grasping Virtual Objectsmentioning
confidence: 99%
“…We built a custom experimental framework using the Oculus DK2 VR headset and the Leap Motion device. Additionally, we used a Logitech Pro 1080p HD webcam positioned on top of the Oculus DK2, based on the methodology of [8] to record participants' hand from the user's perspective at all times. The system was developed using C#, Unity 2018.2 and Leap Motion 4.0 SDK.…”
Section: Experiments 1 [E1] 31 Apparatusmentioning
confidence: 99%